Antiinflammatory phytochemicals against virus‐induced hyperinflammatory responses: Scope, rationale, application, and limitations. (19th July 2021) - Baranwal, Manoj; Gupta, Yogita; Dey, Priyankar; Majaw, Suktilang
Abstract : Uncontrolled inflammatory responses or cytokine storm associated with viral infections results in deleterious consequences such as vascular leakage, severe hemorrhage, shock, immune paralysis, multi‐organ failure, and even death. With the emerging new viral infections and lack of effective prophylactic vaccines, evidence‐based complementary strategies that limit viral infection‐mediated hyperinflammatory responses could be a promising approach to limit host tissue injury. The present review emphasizes the potentials of antiinflammatory phytochemicals in limiting hyperinflammatory injury caused by viral infections. The predominant phytochemicals along with their mechanism in limiting hyperimmune and pro‐inflammatory responses under viral infection have been reviewed comprehensively. How certain phytochemicals can be effective in limiting hyper‐inflammatory response indirectly by favorably modulating gut microbiota and maintaining a functional intestinal barrier has also been presented. Finally, we have discussed improved systemic bioavailability of phytochemicals, efficient delivery strategies, and safety measures for effective antiinflammatory phytotherapies, in addition to emphasizing the requirement of tightly controlled clinical studies to establish the antiinflammatory efficacy of the phytochemicals. Collectively, the review provides a scooping overview on the potentials of bioactive phytochemicals to mitigate pro‐inflammatory injury associated with viral infections.